Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan PT. Budi Mandiri Kencana - Hasibuan, Nurhanima; Saputra, Hendra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Financial performance is the initial window of attention of shareholders and investors, so it is important to monitor the growth of financial performance to be better. This study aims to analyze the financial performance of PT. Budi Mandiri Kencana using financial ratios, including the Liquidity ratio, Profitability ratio and Solvency ratio. The analysis uses a quantitative descriptive approach, which will describe the condition of the research object based on the results of statistical tests. The type of data is secondary data obtained from the company's financial data during the period 2021-2023. The results of the study show that the company's financial performance is in good and strong condition, although there are weaknesses in the Liquidity ratio where the company is very dependent on debt in the company's operations. However, this can be supported by a good Profitability ratio, so that payment of obligations can still be met. However, the company must still pay attention to this deficiency by evaluating liquidity management, avoiding increased risk and smooth operations.